2013
DOI: 10.3906/tar-1206-37
|View full text |Cite
|
Sign up to set email alerts
|

Combustion properties of medium-density fiberboards coated by a mixture of calcite and various fire retardants

Abstract: The properties of wood and wood-based panels may be affected by many factors, such as fungi, insects, humidity, and fire. For reducing these influences, wood and woodbased panels can be treated with various chemicals, including a PVC-based layer and various dyes, or coated with wood veneers or foils, depending on the structure of the material and its intended use. Generally, the panels are coated in order to increase the areas in which they can be used, improve their strength characteristics, and enhance their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
2
5
1
1
Order By: Relevance
“…The highest residual char amounts were obtained from ammonium sulfate for poplar and Scots pine; zinc borate for beech; borax for alder,. Boron materials as fire retardant chemicals were investigated by several researchers during the last decades (Tomak et al 2012, Tondi et al 2014, Salman et al 2014, Yuksel et al 2014, Istek et al 2013, Roth et al 2007, Jin et al 2014, Qu et al 2011. Parallel to the previous studies, our results showed that the impregnation of boron materials (Zinc borate and borax) enhanced the resistance against fire (Uner et al 2016).…”
Section: Thermogravimetric Analyzes (Tga)supporting
confidence: 79%
“…The highest residual char amounts were obtained from ammonium sulfate for poplar and Scots pine; zinc borate for beech; borax for alder,. Boron materials as fire retardant chemicals were investigated by several researchers during the last decades (Tomak et al 2012, Tondi et al 2014, Salman et al 2014, Yuksel et al 2014, Istek et al 2013, Roth et al 2007, Jin et al 2014, Qu et al 2011. Parallel to the previous studies, our results showed that the impregnation of boron materials (Zinc borate and borax) enhanced the resistance against fire (Uner et al 2016).…”
Section: Thermogravimetric Analyzes (Tga)supporting
confidence: 79%
“…Compared with similar studies using MDF (Istek et al 2013;Özçifci and Okcu 2008), the values determined in the present study were higher. The effect of BA on the fire property of the particleboard was greater than that of the BX, MEL, and DOL.…”
Section: Fire Performancecontrasting
confidence: 47%
“…The highest residual char content (75%) was achieved for the sample impregnated with 4,70% DOT among the all treated samples. Fire retardancy of borates were investigated by several researchers during the last decades (Tomak et al 2012, Tondi et al 2014, Salman et al 2014, Yuksel et al 2014, Istek et al 2013, Roth et al 2007, Jin et al 2014, Qu et al 2011). Parallel to the previous studies, our results showed that the impregnation of borates (BX, BA, BA+BX (1:1), BA+BX (7:3) and DOT) enhanced the resistance against to fire.…”
Section: Resultsmentioning
confidence: 99%